Hukum Fee Kafālah di Lembaga Keuangan Syariah Perspektif Fikih - Maksum, Muh. (Invest Journal of Sharia & Economic Law, 2022)
The contracts in Fiqh Muamalah have all been implemented in Sharia Financial Institutions. One of the implemented contract products is kafālah. Kafālah is a binding contract between a kāfîl (guarantor) to a guaranteed party (makfūl lah) for the receivables given for the implementation of a project/work. In Islamic Financial Institutions, the kafālah contract is applied as a Bank Guarantee, Letter Of Credit and Sharia Credit Card (Syariah Card). Contract products that use the kafālah system all have a fee. However, the problem is that many people are confused about the law on the existence of the kafālah fee. This paper describes the law, basis and reasons for Ulam related to kafālah fees implemented in Islamic Financial Institutions. This research uses a type of literature research or library research, namely by collecting data that is the main source from various books, books, articles, scientific journals, and other writings related to the kafālah. The approach taken by the researcher is using a qualitative approach, where the data collected is not in the form of numbers, but the data is obtained from the study and review of literature on bibliographic sources. The results of the analysis of researchers related to the law of kafalah fees in Islamic Financial Institutions from the perspective of fiqh are different in the opinion of scholars (ikhtilaf). A kafālah contract is a tabarru contract (charity program), not a tijari contract entitled to a fee. This principle makes some Fiqh scholars not allow a kāfîl to take a fee for insurance services given to the makfūl 'anhu. However, some scholars allow fees on kafālah contracts because of the condition of a general-purpose, so that if there is no fee, it will not realize the benefit and carry out good deeds.